2015
DOI: 10.1016/j.egypro.2015.01.051
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Methane Potential for the South Sumatra Basin Coal: Formation Water Screening and Coal Substrate Bioavailability

Abstract: Formation water samples collected from five South Sumatra Basin (SSB) coal bed methane (CBM) wells were investigated for the presence of active microbial communities capable of converting coal to methane using culture enrichment studies and molecular phylogenetics techniques. All water samples contained communities capable of methanogenesis using both acetoclastic and hydrogenotrophic pathways. In addition, viable coals to methane communities were detected in four of the water samples. Molecular analysis furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…The enrichment cultures showed increasing CH 4 production over time with both hydrogenotrophic and acetoclastic pathways active (see Susilawati et al, 2015a;2015b). Overall CH 4 production from substrate tubes (coal, acetate, H 2 +CO 2 ) was higher than from the nocoal/no substrate control tubes (Tables 4, 5 and 6).…”
Section: Ch 4 Production and Methanogenic Substrate Screeningmentioning
confidence: 93%
See 4 more Smart Citations
“…The enrichment cultures showed increasing CH 4 production over time with both hydrogenotrophic and acetoclastic pathways active (see Susilawati et al, 2015a;2015b). Overall CH 4 production from substrate tubes (coal, acetate, H 2 +CO 2 ) was higher than from the nocoal/no substrate control tubes (Tables 4, 5 and 6).…”
Section: Ch 4 Production and Methanogenic Substrate Screeningmentioning
confidence: 93%
“…Molecular DNA analysis showed that SSB formation waters contained diverse bacterial and archaeal communities that were able to generate CH 4 using different substrates including coal, acetate and H 2 +CO 2 (Figure 2) (Susilawati et al, 2015a (Susilawati et al, 2015a;2015b). At the genera level, Methanosarcina and Methanosaeta were the most prevalent archaeal methanogens in the SSB water, followed by Methanobacterium and Methanoregula.…”
Section: Microbial Methanogen Consortiamentioning
confidence: 99%
See 3 more Smart Citations